(untitled) (Eurasian Journal of History, Geography and Economics, 2024)
The Prophet’s biography, or the life of Prophet Muhammad (peace be upon him), is considered one of the essential elements and main focal points in interpreting early Islamic history. It represents a fundamental source for understanding and analyzing the circumstances and events surrounding the emergence of Islam and the building of the first Islamic state. Through the study of the Prophet’s biography, we open a wide window onto the events and transformations that the Islamic nation underwent in its beginnings. The Prophet’s biography provides a comprehensive insight into the social, political, and cultural context in which Islam arose. It reveals the impact of the Prophet Muhammad’s actions and stances in shaping the trajectory of the early Islamic nation. Understanding the Prophet’s biography extends beyond merely recording historical events; it encompasses a deep understanding of the values and principles carried by Islam through the life and example of the Prophet. It serves as a model for Islamic leadership and provides guidance for Muslims in dealing with various challenges, whether internal or external. In this research, we will shed light on the role of the Prophet’s biography as a crucial link in understanding and documenting early Islamic history. We will trace and analyze the stages of interest in and documentation of his biography, and how it influenced the paths of Islamic history and its development, to discover the importance and impact of this pivotal element in shaping early Islamic identity and development